Legal Protection for Consumers Using Shopee Paylater Cash Swipe Services - Sri Astutik, Dinda; Hardian Iskandar (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
In the current digital era, there are many benefits, one of which is electronic commerce transactions that provide various attractive features such as Paylater or pay later. This writing uses a normative legal writing method. Where a legislative approach will be taken by reviewing laws and regulations with the use of the Paylater feature. The increasing online purchasing power is now widely used by individuals who use the Paylater feature to make Cash Swipes, legal protection for users of cash swipe services is very important. Cash Swipe is a practice that involves disbursing credit limits from digital platforms such as Shopee Paylater in cash. This practice often causes legal problems and threats to consumers, such as fraud, increased debt, and misuse of personal data. The purpose of this study is to see how Law Number 8 of 1999 concerning Consumer Protection protects consumers who use Shopee Paylater swipe cash services. In addition, this study also investigates the responsibility of platform providers to protect customers from detrimental practices. The results of the study show that the practice of gestun violates legal provisions related to financial transactions and consumers. Consumers involved in this practice also do not get protection from service providers and consumers will also get violations of the law.